Advanced design and manufacture III : selected, peer reviewed papers from the 3rd International Conference on Advanced Design and Manufacture (ADM2010), 8-10 September 2010, Nottingham, UK - Su, Daizhong; Zhang, Qingbin, 1964-; Zhu, Shifan, 1963- (Key engineering materials ;, 2011)
This volume comprises a prestigious collection of refereed papers selected from those submitted to the 3rd International Conference on Advanced Design and Manufacture (ADM2010), held of the 8th to the 10th of September, 2010, in Nottingham, UK. This conference was hosted by Nottingham Trent University and was jointly organized by Nottingham Trent University, Harbin Engineering University and the Harbin Institute of Technology. The major topics covered by the conference themes, as reflected by the present papers, included: Product/industrial/engineering design, CAD/CAM/CAE, Computer simulation.